Avaliação dos parâmetros de crescimento, metabólicos e antioxidantes de juvenis de jundiá (Rhamdia quelen) alimentados com dietas contendo peptídeos funcionais obtidos de larvas de Tenebrio molitor - (:unkn) unknown (Universidade Federal do Pampa, 2023)
Aquaculture stands out as the production of high quality protein in more sustainable crop systems, ensuring food security. In this sense, for fish farming to become a competitive activity, there is a need for intensification, however, in parallel to the intensification of production, several factors favor the stress of animals, which make them more susceptible to the development of diseases. Thus, bioactive peptides arrive as an alternative to antibiotics and can be used as functional or nutraceutical ingredients. The objective of this study was to evaluate the effect of the inclusion of increasing levels of bioactive peptides obtained from Tenebrio Molitor (PBTM), in the diet of jundiá juveniles, on growth parameters, intermediate metabolism and antioxidant. For this, three experimental diets were formulated containing increasing levels of bioactive peptides of T. Molitor, 0% (control diet), 0.5% PBTM and 1% PBTM. At the end of the nutritional trial, the fish underwent prior fasting, anesthesia for weighing and measurement to estimate the following parameters: final weight (FW), specific growth rate (SGR), daily weight gain (DWG), relative weight gain (RWG) and food efficiency index (FEI), after euthanized by eugenol overdose for liver collection. Among the hepatic biochemical analyzes it was possible to determine protein levels, as well as antioxidant parameters such as catalase (CAT), glutathione S-transferase (GST), thiobarbituric acid (TBARS) and mucus scraping for determination of mucoproteins. No significant differences were observed in relation to growth parameters such as FP, TCE, GPD and GPR; the control group fish presented higher IEA ((52,37±5,16c). The fish that received the diet 1.0% PBTM showed higher alanine aminotransferase activity (22,33±2,68b); the enzymes CAT, GST had no significant difference and was observed higher levels of TBARS in the jundias of the group with 0.5% PBTM. The bioactive peptides of T. Molitor larvae did not promote negative effects on the performance of the animals, in addition, the liver parameters remained stable, and the inclusion of 1.0% of PBTM in the diets promoted improvements in the protection against lipid peroxidation.
Evaluation of growth, metabolic and antioxidant parameters of jundiá (Rhamdia quelen) juveniles fed diets containing functional peptides obtained from Tenebrio molitor larvae
Keywords: Bioactive peptides; Intermediate metabolism; Antioxidant enzymes; Rhamdia quelen; Peptídeos bioativos; Metabolismo intermediário; Enzimas antioxidantes; Aquicultura; CNPQ::CIENCIAS AGRARIAS